EMPLOYEE SATISFACTION WITH SOCIAL SECURITY PROVISIONS (GRATUITY, PF, AND PENSION): AN EMPIRICAL STUDY IN THE SELECTED ORGANIZATIONS (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2023)
In a developing country like India, social  security provisions and measures have a two fold significance. Social security provisions  constitute essential steps towards the aim of a  welfare state by bringing improvements in the  living standard and safeguarding people from  uncertainties that may arrive in the future. The  Human Resource Management department in  companies is worried about the management of  people at the workplace, and it is essential for  them to secure the cooperation of workers and  employees to increase productivity and to earn  good profits. The productivity of employees will  be high only if they are delighted with their  employer and with the working environment  at their workplace. Good and satisfactory  social security provisions will make employees  satisfied with their jobs and will improve  their performance as well. Someone who feels  safe and satisfied with their jobs gives good  performance and improves the production  at their job.A sample of 250 respondents was  collected from respondents.
Keywords: Social Security; Provident Fund; Retirement; Gratuity; Labor Welfare; Job Satisfaction